ความคุ้มค่าทางการเงินของการผลิตเห็ดแบบครบวงจร ในจังหวัดเชียงใหม่ - ปรียานุช ชุ่มเชื้อ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The financial worthiness of the Integrated mushroom farm production in Chiang Mai province has the objective to know the nature Integrated mushroom farm production. Study by collecting data from 2 mushroom farm owners is medium farm and large farm. Using the analysis considered the possibility of investing in a cash flow analysis and considered the financial worth of the project. This is determined by a measure of the cost of the project by following: The payback period (PB), net present value (NPV), internal rate of return (IRR), benefit cost ratio (BCR) and assessed the financial risk of investment project , by sensitivity analysis test method. by setting the duration of the project is 10 years and a discount rate equal to 8.00 percent per annum from interest rate loan which is comparison between 2 mushroom farms medium and large farm (medium farm: building size 5x10 meter, large farm: building size 6x20 meter) From the study of costs and benefits of the integrated mushroom farm production, large and medium sized farm found that the large size farm has the cost initial investment 3,673,400 Baht and the cost of operation each year on average between 1,411,935 to 1,423,935 Baht and average total revenue 3,208,100 Baht. The medium size farm has the cost initial investment 3,461,600 Baht and the cost of operation each year on average between 524,009 to 537,589 Baht and average total revenue 1,470,375 Baht A study of the financial worthiness of Integrated mushroom farm production large and medium sized farm found that the large size farm has net present value (NPV) is 8,361,331 Baht, internal rate of return (IRR) is 48.00 percent, benefit cost ratio (BCR) is 1.62 and payback period (PB) is 2.05 .The medium size farm has net present value (NPV) is 2,842,492 Baht, internal rate of return (IRR) is 24.00 percent, benefit cost ratio (BCR) is 1.41 and payback period (PB) is 3.67 . In addition, results from testing the variation of the large and medium showed that the cost of the two projects could be increased percentage of 53.24 and 40.55 respectively, while the income of the two projects can be reduced most 34.84 and 28.81 percent, respectively, concluded that large projects are worth the investment and lower financial risk over the medium size farm.